Towards ‘Creative Participatory Science’: Exploring Future Scenarios Through Specialist Drought Science and Community Storytelling - Liguori, Antonia; McEwen, Lindsey; Blake, James; Wilson, Michael (Frontiers in Environmental Science, 2021)
There is a growing interest in different forms of participatory modelling that bring science and lay knowledge into the same space. This recognises that, traditionally, the environmental science community has mostly seen stakeholder engagement as a ‘follow on’ activity to be undertaken once the key scientific research has been completed. By excluding communities from the scientific process, or at best approaching communities in one-way communication, scientists are missing out on the wealth of local community knowledge about the very facets of the environment which they seek to understand. The challenge, however, is in identifying, developing and adopting appropriate platforms for communication and co-creation to allow scientists and local communities to have effective dialogue, efficiently gather, interpret and evaluate lay knowledge, and develop relevant, scientifically robust, but widely comprehensible, results. DRY (Drought Risk and You) was a 4-year project, funded under the RCUK Drought and Water Scarcity Programme, with the aim of developing an evidence-based resource to support better decision-making in UK drought risk management. In DRY, scientific data and multiple narrative approaches have been brought together to facilitate decision-making processes and improve community resilience. Creative experiments were designed to engage local communities in using specialist science as a stimulus for storytelling at catchment level, but also to give scientists the insight required to develop meaningful scenarios of local change. One challenge of working with storytelling is that it is very often retrospective and linked to past experiences and memories. The participatory approaches applied in DRY demonstrated that storytelling can be also used to imagine, interrogate and plan for a future that communities might collectively wish to subscribe or adapt to. In particular, by co-designing and facilitating storyboarding workshops, the DRY team, together with local stakeholders, have been exploring the ‘scenario-ing’ of possible futures as a way of creating a story and visualising a picture for the future of the community. By allowing the scientists, community and local stakeholders to develop model drought scenarios iteratively together using storytelling, these scenarios should not only be scientifically accurate, but should also reflect local interests and aspirations, as well as local drought mitigation practices.